2005
DOI: 10.1152/japplphysiol.00984.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differences in time-dependent hypoxic phrenic responses among inbred rat strains

Abstract: . Differences in time-dependent hypoxic phrenic responses among inbred rat strains. J Appl Physiol 98: 838 -844, 2005. First published November 5, 2004; doi:10.1152 doi:10. /japplphysiol.00984.2004 responses differ between rodent strains, suggesting a genetic contribution to interindividual variability. However, hypoxic ventilatory responses consist of multiple time-dependent mechanisms that can be observed in different respiratory motor outputs. We hypothesized that strain differences would exist in discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…However, prior work indicated that moderate CO 2 reductions during hypoxia do not prevent respiratory STP (Song and Poon 2009), and indeed, a robust STP of phrenic activity was observed during and after hypoxia. In addition, the magnitude of the acute hypoxic phrenic response reported here is both quantitatively and qualitatively similar to prior reports in which strict isocapnia was maintained (Fuller 2005;Golder et al 2005). Finally, we confirmed in additional experiments that the drop in PaCO 2 during hypoxia did not significantly alter the expression of phrenic STP.…”
Section: Arterial Blood Gases and Cardiovascular Responsessupporting
confidence: 91%
See 2 more Smart Citations
“…However, prior work indicated that moderate CO 2 reductions during hypoxia do not prevent respiratory STP (Song and Poon 2009), and indeed, a robust STP of phrenic activity was observed during and after hypoxia. In addition, the magnitude of the acute hypoxic phrenic response reported here is both quantitatively and qualitatively similar to prior reports in which strict isocapnia was maintained (Fuller 2005;Golder et al 2005). Finally, we confirmed in additional experiments that the drop in PaCO 2 during hypoxia did not significantly alter the expression of phrenic STP.…”
Section: Arterial Blood Gases and Cardiovascular Responsessupporting
confidence: 91%
“…The potential impact of urethane anesthesia on STP is not certain. However, respiratory STP occurs in both anesthetized animals (e.g., current data; Golder et al 2005;Hayashi et al 1993) and conscious humans (Fregosi 1991) and animals (Kline et al 2002;McGuire 2008). Urethane was selected as the anesthetic in this study because robust hypoxic phrenic responses occur in urethane anesthetized rats (Bach and Mitchell 1996;Baker-Herman et al 2004).…”
Section: Critique Of Methodologymentioning
confidence: 96%
See 1 more Smart Citation
“…Differences among inbred rat strains (1), as well as differences between inbred and outbred rat strains (2), have been documented during eupnea, hypoxia, hypercapnia, and exercise (2,3). Some of these differences are associated with genotypic differences localized on specific chromosomes (3).…”
Section: Introductionmentioning
confidence: 99%
“…Strain differences in the acute response to hypoxia (11,25), hypercapnia (12,18), episodic hypoxia (3), and the posthypoxic frequency response (2,19) have been reported suggestive of a genetic component to these responses. Several studies involving the control of breathing in inbred strains of mice have identified regions on mouse chromosomes 1, 3, 5, and 9 to which specific breathing phenotypes can be linked (17,20,22,23).…”
mentioning
confidence: 99%